A Review of Sharia Economic Law on the 1982 MUI Fatwa on the Allocation of Zakat Funds for Productive Activities and Public Welfare - Royani; Dede Andriyana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research examines the Fatwa of the Indonesian Ulema Council (MUI) issued in 1982, which allows the disbursement of zakat funds for productive activities and general welfare, viewed through the lens of Sharia Economic Law. The study aims to analyze the fatwa's alignment with Sharia principles, its implementation challenges, and its socio-economic impacts. Employing a qualitative approach with a literature review design, the research analyzes the fatwa text, relevant literature, and related legal and economic frameworks. The findings reveal that the fatwa aligns with the principles of maslahah (public interest) in Sharia, promoting economic empowerment and social justice through productive zakat utilization. However, the implementation faces challenges, including varying interpretations of productive activities, potential misuse of funds, and limitations in institutional capacity. The study highlights the positive impacts of productive zakat on community welfare, including increased income, job creation, improved access to education and healthcare, and infrastructure development. Recommendations include strengthening zakat management, developing community-based economic empowerment programs, clarifying regulations, enhancing public understanding, and conducting continuous evaluations to optimize the effectiveness of zakat in achieving social and economic development goals in accordance with Sharia principles.